Development of a nomogram for predicting postoperative Hirschsprung-associated enterocolitis - Zheng, Weijun; Chen, Weiming; Chen, Fei; Wang, Yunjin; Zhu, Lanxin; Liu, Mingkun (Frontiers in Pediatrics, 2025)
ObjectivesTo analyze the risk factors for postoperative Hirschsprung-associated enterocolitis (HAEC) and establish a nomogram to predict the incidence of HAEC.MethodsAll patients with Hirschsprung disease who underwent definitive surgery at Fujian Provincial Children's Hospital from January 2015 to December 2023 were included in the study. Univariate and multivariate logistic regression were used to analyze the influencing factors of chylous ascites and a nomogram was established. The predictive performance of the nomogram was evaluated using receiver operating characteristic (ROC) curves, calibration plots, and decision curve analysis (DCA) curves.ResultsOf the included 204 patients, 53 patients (25.9%) experienced postoperative HAEC. Preoperative HAEC, the type of HSCR (long-segment or total colonic aganglionosis), no-preoperative bowel preparation, and anastomotic leaks or strictures were considered important risk factors. The area under the ROC curve of the model is 0.79, the nomogram has great discriminative ability, calibration and significant clinical utility.ConclusionWe found a nomogram for predicting the postoperative HAEC. It can be used as a reference for risk assessment and early detection of postoperative HAEC.